Effect of State Government Intervention on Human Capacity Development of Women in North Senatorial District, Adamawa State, Nigeria - Mary Vincent (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examined the effect of Adamawa State Government’s interventions on the human capacity development of women across the Northern Senatorial District of the state. The study was motivated by the persistent marginalization of women resulting from socio-cultural, economic, and political barriers that inhibit their access to development opportunities. A projected 2025 female population of 569,976 across five local government areas of Madagali, Maiha, Michika, Mubi North, and Mubi South constituted the study population. Using the Taro Yamane’s formula, a sample size of 399 was derived and increased to 439 (10% addition) to account for non-response. Stratified random sampling and purposive sampling techniques were adopted to ensure adequate representation of women who directly benefited from government interventions. Primary data was collected using a structured questionnaire designed on a five-point Likert scale, while validity was ensured through expert review and reliability confirmed with Cronbach Alpha values above 0.80. Data were analyzed using descriptive statistics, Pearson correlation, multiple regression, and ANOVA with the aid of SPSS 23.0. The findings revealed that government educational development interventions significantly enhanced women’s human capacity development (β = 0.943, p < 0.001). Economic empowerment interventions also had a strong positive effect (β = 0.607, p < 0.001), The study concludes that state government interventions are pivotal in enhancing the knowledge and political participation of women in Adamawa Northern Senatorial District, Nigeria. It recommends for sustained investment in women’s education, expansion of economic empowerment schemes, promotion of women’s political inclusion, strengthening of gender sensitive policies, and improved healthcare access to foster inclusive and sustainable human capacity development across the state.